Sources and Routes of Introduction of Eimeria Oocysts into Broiler Chick`s Houses - Kiani, Rezvan; Rasadi, Manijeh; Mohammadian, Mohammad N. (International Journal of Poultry Science, 2007)
Coccidiosis in chickens is one of the major problems of poultry industry that is caused by protozoan parasites of genus Eimeria. It is responsible for significant economic losses to the worldwide poultry industry. Eimeria spp. oocysts can be spread to poultry houses by mechanical routes such as boots, dust, cloths, wheels, contaminated equipments and personnel. The objective of present study was to determine which of the above-mentioned parameters is more important. For this purpose a total of 480 samples were collected from litters, workers` hands and boots, wheelbarrows, dust around the houses, feed ingredients and stacked limes situated in front of houses in 5th week of rearing period. The samples were taken from 60 houses related to 30 broiler farms, which were not vaccinated against Coccidiosis. Based on the presence of Eimeria oocysts, the results indicated that dust around the houses, boots, wheelbarrows, litter, feed ingredients and workers` hands identified to be contaminated with Eimeria oocyts were in 39 (65%), 31 (51.7%), 27 (45%), 23 (38.3%), 10 (17%) and 5 (8.3%) cases respectively. In samples taken from stacked limes, Eimeria oocysts were not observed in any cases.